Genetic divergence among Hariana crosses with exotic dairy breeds - Dutt, Triveni; Kumar, N Saravana (The Indian Journal of Animal Sciences, 2012)
This study was undertaken to estimate the genetic divergence among 112 Friesian + 112 Hariana (FH), 112 Friesian + 1/4 Brown Swiss + 1/4 Hariana (FBH) and 1/2 Friesian + 114 Jersey + 1/4 Hariana (FJH) crossbreds, on the basis of first lactation and lifetime traits. Data on 227 FH, 187 FBR and 197 FIR crossbreds from the institute herd during 1976 and 1994 were used to study genetic divergence among 3 genetic groups. The traits included were age at first calving (AFC), first lactation milk yield (FLMY), first peak yield (FPY), first dry period (FDM), first calving interval (FCI), lifetime milk yield (LTMY) and herd life (HL). Only DH·FJH combination showed significant differences for the D² value, based on first lactation and lifetime traits. The FBH genetic group did not differ significantly from FH and FJH. Three genetic groups had formed individual clusters. The total D² values contributed by all the 7 traits is 0.61. The percentage contribution of LTMY to the total D² value was the maximum (36.31%) followed by FLMY(17.71%), FPY (16.08%) and AFC (14.72%).